Needs Analysis of Problem Solving Based Learning Video Development to Train Students' Concept Understanding - Yenni Lestari; M Rahmad; Zulfarina Zulfarina (Pendidikan Kimia Unimus, 2021)
Students' understanding of concepts is a very important factor in the success of learning. But in reality, Indonesian students' conceptual understanding is still low. The factor of low understanding of students' concepts is because students are not actively involved in problem solving activities. Student involvement can be trained by using one of the communication tools in the form of interesting learning videos to get students' attention in learning activities. This research is a survey research as a first step in developing problem solving learning videos. The benefit of this research is to find out what students currently need in science learning and how much students need to develop problem solving based learning videos. The subjects used in this study were junior high school students with a sample size of 48 students selected based on a region. This needs analysis includes 4 indicators, namely a) analysis of learning problems; b) analysis of learners; c) analysis of objectives; d) analysis of settings. Based on the results of this study, information was obtained that the development of problem solving based learning videos was feasible to be developed as a science learning media to train students' conceptual understanding in the city of Pekanbaru